1998
DOI: 10.1007/s004200050266
|View full text |Cite
|
Sign up to set email alerts
|

Urinary cotinine as a tobacco-smoke exposure index: a minireview

Abstract: A minireview is presented concerning the use of cotinine as a tobacco-smoke exposure index. First, general considerations about methods for the determination of urinary cotinine are presented. Besides pure analytical aspects, this minireview considers major problems encountered in the establishment of threshold values that can be used to distinguish not only smokers from nonsmokers but also nonsmokers exposed or not exposed to environmental tobacco smoke (ETS). In addition, the use of urinary cotinine is illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
153
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(160 citation statements)
references
References 92 publications
3
153
0
4
Order By: Relevance
“…The thresholds for classification as current smoker/non-smoker were based on published reports. For cotinine concentration, 539 nmol/l (100 ng/ml) was used as the discriminator between 'current smokers' and 'non-smokers', 2 and for the cotinine/creatinine ratio (CCR) 610 (1 µg /mg in traditional units) was used as the discriminator. 1 The degree of agreement between categories was assessed using the kappa statistic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thresholds for classification as current smoker/non-smoker were based on published reports. For cotinine concentration, 539 nmol/l (100 ng/ml) was used as the discriminator between 'current smokers' and 'non-smokers', 2 and for the cotinine/creatinine ratio (CCR) 610 (1 µg /mg in traditional units) was used as the discriminator. 1 The degree of agreement between categories was assessed using the kappa statistic.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of tobacco smoking, this may lead to under-reporting of the quantity of cigarettes or misclassification of current smokers as ex-or non-smokers. Despite this, studies in urban Westernised environments have shown that the validity of self-reported cigarette smoking is reasonably accurate in most settings [1][2][3][4] (except in some hospital and adolescent settings 5 ) and self-report has been recommended for assessment of smoking in epidemiological studies where associations of smoking are being examined. 6 Cigarette smoking has been reported to be very common among Aboriginal Australians living in remote communities, with current smoking rates of 60-70% reported in some communities in northern Australia.…”
mentioning
confidence: 99%
“…Cotinine (CT) is afterwards further metabolized into several sub-metabolites, making that only 10-15% of consumed nicotine is excreted as cotinine. Cotinine has been used as an indicator of tobacco exposure (Haufroid et al, 1998) and will be evaluated as such in this study. Nicotine itself was not investigated as this compound may enter into WW influents through cigarette stubs disposal.…”
Section: Nicotinementioning
confidence: 99%
“…The urinary creatinine excretion markedly increases between the age of 6 and 19 years (Ciba Geigy AG, 1985). Furthermore, children may have higher cotinine levels than adults due to a slower nicotine metabolism and a higher ventilation rate (Haufroid and Lison, 1998). Therefore, age must be considered when comparing the urinary cotinine levels of children.…”
Section: Etsmentioning
confidence: 99%
“…A reanalysis of these samples with GC resulted in substantially lower cotinine concentrations: 22 samples had levels of 420 ng/ml (mean: 50 ng/ml), no sample was 4100 ng/ml. The cut-off levels for urinary cotinine in order to differentiate nonsmokers from smokers were reported to be 50-100 ng/mg (60-120 ng/ml, determined with RIA (Haufroid and Lison, 1998)) and 20-100 ng/ml (method not specified (Haufroid and Lison, 1998)). Even if the GC-determined cotinine concentrations were taken as a basis, some of the observed high cotinine levels are conspicuous.…”
Section: Etsmentioning
confidence: 99%